JAVA TRADITIONAL COMMUNITY WEDDING CEREMONY TRADITION IN BANDAR JAWA III HUTA, BANDAR SUB-DISTRICT, SIMALUNGUN REGENCY - Sutikno Sutikno; Harianto II; Rahmat Kartolo; Rosmawati Harahap; Rahmadi Ali (Sosiohumaniora, 2022)
This research aimed at describe the tradition of the Javanese traditional community wedding ceremony at Huta III Bandar Jawa, Bandar Subdistrict, Simalungun Regency. This research used descriptive qualitative approach. The results of the research were carried out by observation, interviews, and documentation. This research found that the Javanese traditional wedding tradition in Huta III generally consists of eleven processions, namely 1) peningsetan, 2) saserahan, 3) pasangtarub or tratag, 4) malamlamaran, 5) kerik-an, 6) ijabkabul, 7) temumanten, 8) lemparsirih, 9) injaktelur (wijidadi), 10) sungkeman, 11) tepungtawar and marhaban. The tradition of Javanese traditional ceremonies in Huta III is not the same as the wedding traditions in Central Java, there are several traditions or processions that have been abandoned. Not only that, the Javanese traditional wedding tradition in Huta III has now experienced a combination or acculturation of the surrounding culture, one of the acculturations of the Malay culture which has now been adopted or carried out by the Javanese people of Huta III in the Javanese traditional wedding procession.